Literary Experience as (Visual) Experience of Literary Worlds. Imagination’s Bearing on Literary Reality and Phantasy’s Bearing on Literary Existence - Bellini, Bianca (Res Cogitans, 2018)
While reading literary works, what do readers experience? Do they experience only the words they listen to or read? How can we describe the experience of reading literary works? Do phantasy and imagination play any role during such experiences? These kinds of questions usually give rise to a twofold kind of research: on the one hand, a philosophical effort of combing through literature itself as a philosophical object of study, and — on the other hand — an attempt to argue for a cognitive portrait of those processes triggered by reading or listening to words (cf. Dehaene, 2007). Nevertheless, if we put aside these two sets of studies, which are plenty widespread and partly related to scientific branches, three new and interwoven ways of broaching the issue of literary experience come to light: 1) readers’ experiences of literary worlds; 2) readers’ visual involvement in literary experiences; 3) phantasy’s and imagination’s involvement in such experiences. These issues are strongly interwoven since each of them deals with the experience of reading literary works from slightly different perspectives: the first concerns the objects of literary experiences, the second focuses on a specific component of literary experiences, while the third aims at comprehending what role is up to phantasy and imagination during such experiences. The following research purports to answer the aforementioned questions and, in so doing, it develops and argues for the following thesis, which is the heart of the matter: reading literary works means experiencing literary worlds and, consequently, describing literary experiences means describing the literary worlds we experience while reading literary works.